Entrepreneurial Guidance and Educational Programs for Young University Students in the City of Riobamba - Chávez, Luz Maribel Vallejo; Mosquera, Wilian Pilco; Oleas, María Espín; Vallejo, Patricio Moyano (ESPOCH Congresses: The Ecuadorian Journal of S.T.E.A.M., 2024)
After the growing economic crisis caused by the COVID-19 pandemic, the need for entrepreneurial orientation arises in educational programs at universities. Concept that has been incorporated in universities, as a topic of importance in the different careers and training areas today, in the face of the problem of lack of employment and the crisis, it is therefore essential to work on these concepts. The results of the research in university students were: 56% women, 44% men; 58% at the age of 21-24 years; 98% single, 2% cohabiting; 67% students from (ESPOCH) and 33% from (UNACH). In the entrepreneurship orientation variable, three indicators were measured: (i) short-term goals: 75% of students spend on vacations, 93% spend on parties, 58% spend on clothing; 81% spend on food; 95% spend on their vocational training to obtain a university degree. (ii) medium-term economic goals: 62% would invest in financial entities; 63% would be part of the shares of a company. (iii) long-term goals: 48% would buy a vehicle, and 88% would buy a house or an apartment. In the educational programs variable, 74% have a business initiative; 79% have not yet started a business and have not carried out commercial activities; 70% do not have an account in a financial institution to invest in their own business; 56% would take out a loan to start a business, 67% expect employability to obtain their own business. It is concluded that there is a significant relationship between the entrepreneurial orientation variables and the educational programs. Keywords: educational programs, entrepreneurship, education, development, motivation. Resumen Tras la creciente crisis económica ocasionada por la pandemia COVID-19, surge la necesidad de la Orientación emprendedora en los programas educativos en los universitarios. Concepto que se ha incorporado en las Universidades, como tema de transcendencia en las distintas carreras y áreas de formación que hoy en día ante la problemática de falta de empleo y la crisis es imprescindible trabajar estos conceptos. Los resultados de la investigación en los estudiantes universitarios fueron: 56% mujeres, 44% hombres; 58% en la edad de 21-24 años; 98% solteros, 2% unión libre; 67% estudiantes de la (ESPOCH) y 33% de la (UNACH). En la variable orientación al emprendimiento se midió tres indicadores: (i)metas a corto plazo: 75 % de los estudiantes gastan en vacaciones, 93% gastan en fiestas, 58% gastan en prendas de vestir; 81% gastan en alimentos; 95% gastan en su formación profesional para obtener un título universitario. (ii)metas económicas a mediano plazo: 62% invertiría en entidades financieras; 63% formarían parte de las acciones de una empresa. (iii)metas a largo plazo: 48 % comprarían un vehículo, 88% comprarían una casa o departamento. En la variable programas educativos, 74% tiene iniciativa de un negocio; 79% aún no emprende y no han realizado actividades comerciales; 70% no tiene una cuenta en una entidad financiera para invertir en su propio negocio; 56% realizaría un crédito para emprender, 67% en su expectativa de empleabilidad es obtener su propio negocio. Se concluye que, sí existe una relación significativa entre las variables orientación emprendedora y los programas educativos. Palabras Clave: programas educativos,emprendimiento, educación, desarrollo, motivación.